ANALISIS MANAJEMEN MAKNA TERKOORDINASI DAN PESAN DAKWAH PADA FILM 3: ALIF LAM MIM - Thoriq Azhar Zulkarnain; Siti Ngainnur Rohmah; Sobirin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The film 3: Alif Lam Mim portrays three close friends who strive to uphold truth within a society that rejects religion. The story begins with a terrorist attack at a nightclub that triggers conflict between groups, prompting the government to dissolve all religious organizations and adopt a liberal system. Alif, Herlam, and Mimbo, as devout Muslims, sense inconsistencies in their nation’s historical narrative. They search for the truth hidden by the government in its effort to establish a fully liberal state. Despite many obstacles, they succeed in uncovering the manipulative plan controlling the government and conveying it to the public. This study aims to analyze the denotative and connotative meanings in the film 3: Alif Lam Mim using Roland Barthes semiotic perspective, interpret these meanings in an integrated manner, and identify the religious messages delivered. The study uses a descriptive literature review method with data taken from the film, books, and scholarly articles. The findings show that the film serves as a social critique of chaos caused by reckless political decisions, which result in false freedom and discrimination against religious citizens. The film also conveys messages about emotional control, perseverance, patience, devotion, and justice.